Telling Deaf Lives : Agents of Change - Snoddon, Kristin (Book collections on Project MUSE., 2014)
"The best of the 8th Deaf History International Conference, members of international Deaf communities around the world relate their own autobiographies as well as the biographies of historical Deaf individuals in this engrossing collection"--